Sex Differences in Kappa Opioid Receptor Agonist Mediated Attenuation of Chemotherapy-Induced Neuropathic Pain in Mice - Paton, Kelly F.; Luo, Dan; La Flamme, Anne C.; Prisinzano, Thomas E.; Kivell, Bronwyn M. (Frontiers in Pharmacology, 2022)
Chemotherapy-induced neuropathic pain is a common side effect for cancer patients which has limited effective treatment options. Kappa opioid receptor (KOR) agonists are a promising alternative to currently available opioid drugs due to their low abuse potential. In the current study, we have investigated the effects of Salvinorin A (SalA) analogues, 16-Ethynyl SalA, 16-Bromo SalA and ethyoxymethyl ether (EOM) SalB, in a preclinical model of paclitaxel-induced neuropathic pain in male and female C57BL/6J mice. Using an acute dose-response procedure, we showed that compared to morphine, 16-Ethynyl SalA was more potent at reducing mechanical allodynia; and SalA, 16-Ethynyl SalA and EOM SalB were more potent at reducing cold allodynia. In the mechanical allodynia testing, U50,488 was more potent in males and SalA was more potent in females. There were no sex differences in the acute cold allodynia testing. In the chronic administration model, treatment with U50,488 (10 mg/kg) reduced the mechanical and cold allodynia responses to healthy levels over 23 days of treatment. Overall, we have shown that KOR agonists are effective in a model of chemotherapy-induced neuropathic pain, indicating that KOR agonists could be further developed to treat this debilitating condition.